Strategi Promosi M’Bro Café and Resto di Masa Pandemi Melalui Platform Instagram - Yefta Jati Putranto (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
This research is entitled The Strategies of Promotion From M’Bro Café and Resto During a Pandemic Through the Instagram Platform. The purpose of this research is to determine the growth and sales management of M'Bro Café and Resto. The approach method is used to draw conclusions based on the answers gathered from the interview in order to support the research. The data collection technique uses semi-structured interviews by getting some information through the Instagram platform, which emphasizes phenomena and issues during the pandemic that can enhance economic growth in the Madiun area. Through the direct interview conducted at M'Bro cafes and restos, it can be concluded that the creative contents that have been distributed to customers and the public increase the selling points through photos and videos, there by attracting customers to purchase food and beverages either through delivery, dine-in, or take away. This research proves that the management of M'Bro cafe and resto is committed to running the business consistently with an unyielding spirit, tenacity, and work ethic to maintain the values of the vision and mission of M'Bro cafe and resto..